2021
DOI: 10.1101/2021.04.13.439632
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural basis for the ARF GAP activity and specificity of the C9orf72 complex

Abstract: Mutation of C9ORF72 is the most common genetic cause of amyotrophic lateral sclerosis (ALS) and frontal temporal degeneration (FTD), which is attributed to both a gain and loss of function. C9orf72 forms a complex with SMCR8 and WDR41, which was reported to have GTPase activating protein activity toward ARF proteins, RAB8A, and RAB11A. We determined the cryo-EM structure of ARF1-GDP-BeF3- bound to C9orf72:SMCR8:WDR41. The SMCR8longin and C9orf72longin domains form the binding pocket for ARF1. One face of the C… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 59 publications
2
6
0
1
Order By: Relevance
“…A recent cryo-EM structure of the GAP-competent interaction between Rag-Ragulator and GATOR1 suggested GATOR1 is stabilized by both Rag GTPases in its GAP mode (34). The overall geometry and the role of the Arg finger in the active GATOR1 complex resembles that of FLCN F118D :FNIP2 seen here, as well as that of another longin-domain based GAP, the C9orf72-SMCR8 complex with ARF1 (31). In comparison to GATOR1, the structure of the AFC revealed that FLCN solely interacts with RagC to stimulate GTP hydrolysis.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…A recent cryo-EM structure of the GAP-competent interaction between Rag-Ragulator and GATOR1 suggested GATOR1 is stabilized by both Rag GTPases in its GAP mode (34). The overall geometry and the role of the Arg finger in the active GATOR1 complex resembles that of FLCN F118D :FNIP2 seen here, as well as that of another longin-domain based GAP, the C9orf72-SMCR8 complex with ARF1 (31). In comparison to GATOR1, the structure of the AFC revealed that FLCN solely interacts with RagC to stimulate GTP hydrolysis.…”
Section: Discussionsupporting
confidence: 63%
“…S6B). We also compared the RagC structure to that of Arf1, which is a substrate of another longin domain GAP, SMCR8 ( 31, 32 ). In the Arf1 model, FLCN F118D (Leu 13 and His 14 ) clash with Arf1 residues (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nesse contexto, foi demonstrado que C9ORF72 se liga a RAB1A-GTP para regular o transporte do complexo ULK1, central para a indução da autofagia, à membrana onde se dará a formação dos autofagossomos (Webster et al, 2016). Já a relevância da interação com ARF1 para a autofagia não é clara, uma vez que C9ORF72 nesse caso, parece atuar em conjunto com SMCR8, para inativar ARF1 (Su et al, 2021).…”
Section: Patientsunclassified